Trichophyton as a Rare Cause of Postoperative Wound Infection Resistant to Standard Empiric Antimicrobial Therapy - Sheema Gaffar; John K. Birknes; Kenji M. Cunnion (Hindawi Limited, 2018)
Fungal infections are rare causes of acute surgical wound infections, but Candida is not an infrequent etiology in chronic wound infections. Trichophyton species is a common cause of tinea capitis but has not been reported as a cause of neurosurgical wound infection. We report a case of Trichophyton tonsurans causing a nonhealing surgical wound infection in a 14-year-old male after hemicraniectomy. His wound infection was notable for production of purulent exudate from the wound and lack of clinical improvement despite empiric treatment with multiple broad-spectrum antibiotics targeting typical bacterial causes of wound infection. Multiple wound cultures consistently grew Trichophyton fungus, and his wound infection clinically improved rapidly after starting terbinafine and discontinuing antibiotics.